2018
DOI: 10.1016/j.jvb.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of prosocial motivation on the association between family-supportive supervisor behaviours and employee outcomes

Abstract: This paper examines how family-supportive supervisor behaviours (FSSBs) are associated with employees' in-role job performance and perceived promotability, and how prosocial motivation moderates these associations. We draw on the Work-Home Resources model (W-HR model) to explain the role of family performance as a mediator between FSSBs and employee outcomes. We also propose that prosocial motivation may influence the association between FSSBs and employee outcomes via family performance in such a way that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 81 publications
6
46
0
Order By: Relevance
“…debates (Bergeron, 2007;Bolino & Grant, 2016) as well as empirical research (Lin et al, 2017;Rofcanin, de Jong, Las Heras, & Kim, 2018) on how a 'concern for others' may come at a cost.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…debates (Bergeron, 2007;Bolino & Grant, 2016) as well as empirical research (Lin et al, 2017;Rofcanin, de Jong, Las Heras, & Kim, 2018) on how a 'concern for others' may come at a cost.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(2017) revealed that displaying helping behaviors at work can come at the cost of neglecting family responsibilities at home. The results in Rofcanin et al (2018) showed that employees who are prosocially motivated at work are worse at negotiating family and work responsibilities, and end up displaying lower work performance.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous studies show that family supportive supervisor behaviors in daily management can effectively help employees alleviate their WFC [ 64 ]. These behaviors not only help employees in their work field but also provide support for fulfilling their family responsibilities, which are the key factors in helping employees balance work and family [ 65 ]. However, supervisors’ time and resources are limited, so they cannot provide all their subordinates with the same level of help and support [ 66 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…This suggests that in countries with high (vs. medium and low) GE the negative association between work–family balance satisfaction and TIs of employees will be weaker. Indeed, perceptions of family‐supportive resources of organisations and macro resources of the country are likely to create a synergic effect, feeding off one other to foster greater work–family balance satisfaction and reduced TIs (Rofcanin, De Jong, Heras, & Sowon, 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%